Think-Aloud Protocol (TAP) Analysis: An Investigation of Writing Assessment Tool for High School Teachers - Andik Nur Wijaya; Suparno Suparno; Slamet Supriyadi (Universitas Lampung, 2019)
Teachers experience particular difficulties in learners’ writing activities for academic purposes. Teachers should concern more about this phenomenon. One of the strategies to explore this fact is by determining an assessment procedure to encompass the writing direction during the learners’ writing process. Understanding learners’ difficulties and defining direction to solve those difficulties are significant for teachers to develop writing direction. This research applied a case study method to investigate the directional concern that Indonesian high school teachers’ arranged derived from a think-aloud protocol (TAP) assessment, which the researcher suggested. The researcher interviewed three Senior High School teachers about the argumentative writing performance of their three learners by applying the TAPAssessment. After the TAPassessment, the teachers’ directional concerns contained more elements related to the process of writing, even though they still ignored several significant processes. The inference result was that writing teachers’ professional development gave directional plans so that teachers were facilitated to work on writing assessment data thoroughly for the whole organization aspects. http://dx.doi.org/10.23960/aksara/v20i2.pp55-71